A longitudinal mixed methods study of parents' socioeconomic status and children's educational attainment in Dalian City, China. (January 2017) - Kim, Sung won; Kim, Edward J.; Wagaman, Amy; Fong, Vanessa L.
Highlights: Children of business owner mothers are less likely to get into a prestigious college prep high school and attain a bachelor's degree than children of white-collar mothers. Children of blue-collar fathers are more likely than children ofwhite-collar fathers to get into a prestigious high school and obtain a bachelor's degree. Business owning parents have less time than other parents to tutor their children. Children of "poorer" parents are more motivated than children of "wealthier" parents to gain upward mobility through academic achievement. Abstract: This article examines why most of a cohort that attended eighth or ninth grade in 1999 at a middle school in Dalian City, Liaoning Province, China believed by 2012–2013 that children of poorer parents did better academically than children of wealthier parents. Based on survey data collected from 503 members of this cohort in 1999 and 2012–13, we found that business owners were the wealthiest among respondents' parents, that children of business owner mothers were less likely to get into a prestigious college prep high school and attain a bachelor's degree than children of white-collar mothers, and that children of blue-collar fathers were more likely than children of white-collar fathers to get into a prestigious high school and obtain a bachelor's degree. Based on follow-up interviews with 48 of these respondents, we found that business owning parents had less time than other parents to tutor their children, and that children of "poorer" parents were more motivated than children of "wealthier" parents (most of whom were business owners) to gain upward mobility through academic achievement.